Konservatisme Akuntansi Sebagai Strategi Adaptif Perusahaan Manufaktur dalam Menghadapi Ketidakpastian: Sebuah Sintetik Analitik - Athira Putri Hasmi; Seftriasa Alfadilla Amran; Lestari, Nayla (Journal of Economic Education and Entrepreneurship Studies, 2023)
This study aims to examine and identify the results of research on the application of the principle of accounting conservatism in manufacturing companies in Indonesia. The method used as an analytical tool is a meta synthesis of several research findings on accounting conservatism in Indonesia. The results of this study explain the importance of the principle of conservatism in directing companies to be more careful in the measurement of profits, assets, and recognition of potential losses.  The weakness of accounting conservatism can lead to underreported earnings, can inhibit innovation, and can reduce transparency. The high level of application of the principle of accounting conservatism can lead to conservatism bias. Conservatism bias can be overcome by the way, companies must make an objective assessment of uncertain financial information. Then, the company must apply the principle of conservatism consistently over time.